2019
DOI: 10.1063/1.5109090
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic neuron based on IGZO Schottky diodes for neuromorphic computing

Abstract: Neuromorphic architectures based on memristive neurons and synapses hold great prospect in achieving highly intelligent and efficient computing systems. Here, we show that a Schottky diode based on Cu-Ta/InGaZnO4 (IGZO)/TiN structure can exhibit threshold switching behavior after electroforming and in turn be used to implement an artificial neuron with inherently stochastic dynamics. The threshold switching originates from the Cu filament formation and spontaneous Cu–In–O precipitation in IGZO. The nucleation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…[42][43][44][134][135][136][137][138][139][140][141][142][143] Furthermore, the stochastic neuronal population for performing complex computational tasks such as Bayesian inference may be readily implemented using the memristor as an additive source of stochasticity. [42,135,141] When the electrical input pulse (V INPUT ) is applied to the top electrode, the voltage potential across the memristor progressively accumulates until it reaches a specific threshold (red dotted line in Figure 4a), thus mimicking the IF function. Once it exceeds the threshold, the memristor based on threshold switching can suddenly release its current (I OUTPUT ) to the bottom electrode.…”
Section: Memristive Artificial Neuronsmentioning
confidence: 99%
“…[42][43][44][134][135][136][137][138][139][140][141][142][143] Furthermore, the stochastic neuronal population for performing complex computational tasks such as Bayesian inference may be readily implemented using the memristor as an additive source of stochasticity. [42,135,141] When the electrical input pulse (V INPUT ) is applied to the top electrode, the voltage potential across the memristor progressively accumulates until it reaches a specific threshold (red dotted line in Figure 4a), thus mimicking the IF function. Once it exceeds the threshold, the memristor based on threshold switching can suddenly release its current (I OUTPUT ) to the bottom electrode.…”
Section: Memristive Artificial Neuronsmentioning
confidence: 99%
“…A large number of recent theoretical works have revealed that a single neuron can be used as a highly powerful unit of computation [16][17][18] , whose functionality far exceeds a simple point neuron model. Many of the important functionalities, such as gain modulation, have not been implemented in artificial neurons to date, including Hodgkin-Huxley neurons 19,20 , leaky integrate and fire (LIF) neurons [21][22][23] , and oscillation neurons 24,25 , etc. Beyond the exploration for more capable neuromorphic devices, there are very few reports on integration of artificial synaptic devices with artificial neurons in the same array and hardware construction of a fully memristive neural network for functional demonstrations 26,27 .…”
mentioning
confidence: 99%
“…In addition, when the memristive device is stochastic, a stochastic neuron can be realized based on this structure. [131] Simplified artificial neurons were also proposed: a single device emulated the LIF functions. [132] In a three-terminal structured device, there exists an intrinsic capacitor between the gate electrode and the channel, and the capacitor is used to integrate electric signals.…”
Section: Artificial Neurons Based On Memristive Devicesmentioning
confidence: 99%